Faktor-Faktor Yang Berpengaruh Terhadap Pekerja Yang Menjadi Commuter Dan Tidak Menjadi Commuter Ke Kota Palembang - Novey Afriyani; Lili Erina; Tatang A.M Sariman (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2017)
This study aims to analyze the factors that affect the workers who become commuters and do not become commuter to the city of Palembang. This research was conducted in Palembang City with the number of samples of 70 respondents who became commuter. Hypothesis testing is done multivariate by using logit (binary logistic regresion) model to measure how big independent variable is marital status (MAR), gender (SEX), age (AGE), education level (EDUC), income (WAGE), and distance (DISTANCE) which affects the dependent variable that is a commuter or not a commuter. The value of R square 0,377 means that 37,7% of variation of factors influencing commuter worker or commuter can not be predicted from independent variable. Partially, income variable (WAGE), and distance (DISTANCE) have significant influence while marital status (MAR), gender (SEX), age (AGE), education (EDUC) have no significant effect. The income variable (WAGE) is the most dominant factor to the commuter worker and does not become commuter to Palembang city based on the highest Exp (B) value of 44,847 and has coefficient value 3,803.